Flow control for efficient wind turbine - Muhammad Fariz Abdul Rahman. (2009)
This project aims to model and analyze the different flow control methods to improve the wind turbine efficiency for areas that has high energy consumption, land scarcity and low wind velocity. The model of the shrouded wind turbine is constructed using Solidworks 2008 while the Computational Fluid Dynamic (CFD) simulations were done using ANSYS CFX 11.0. The turbine blade was designed using the Blade Element and Momentum (BEM) theory, using a blade tip speed ratio of λ=6. Since there are limited data and results available for comparisons to the accuracy of the shrouded wind turbine design, a mesh convergence analysis was conducted using four different meshes of the same shrouded wind turbine model, simulating the flow on four different blade tip speed ratio. The Coefficient of Power, Cp, gathered from the simulations, are then compared, to see if flow control using a convergent-divergent duct has any significant difference from the Betz’s Cp Limit of 0.59. It is discovered that the blade of λ=5 has the best coefficient of power of 0.96, thus concluding that flow control using a shrouded converging-diverging duct does increase the efficiency of the wind turbine. Another conclusion can also be made. The turbine blade was designed using λ=6, but the blade with λ=5 has the most optimum Cp, thus, this can be seen that by just using BEM theory alone, the results obtained are insufficient as in reality, the wind seen by a wind turbine is not stationary due to turbulence and wind shear. Hence, using BEM method to design the turbine blades and ANSYS CFX 11.0 to run the CFD simulation, the design of the wind turbine can be adjusted so that the most optimum blade tip speed ratio versus Cp can be realized.